Approaches for Controlling Antibody-Mediated Allograft Rejection Through Targeting B Cells - Matsuda, Yoshiko; Watanabe, Takeshi; Li, Xiao-Kang (Frontiers in Immunology, 2021)
Both acute and chronic antibody-mediated allograft rejection (AMR), which are directly mediated by B cells, remain difficult to treat. Long-lived plasma cells (LLPCs) in bone marrow (BM) play a crucial role in the production of the antibodies that induce AMR. However, LLPCs survive through a T cell-independent mechanism and resist conventional immunosuppressive therapy. Desensitization therapy is therefore performed, although it is accompanied by severe side effects and the pathological condition may be at an irreversible stage when these antibodies, which induce AMR development, are detected in the serum. In other words, AMR control requires the development of a diagnostic method that predicts its onset before LLPC differentiation and enables therapeutic intervention and the establishment of humoral immune monitoring methods providing more detailed information, including individual differences in the susceptibility to immunosuppressive agents and the pathological conditions. In this study, we reviewed recent studies related to the direct or indirect involvement of immunocompetent cells in the differentiation of naïve-B cells into LLPCs, the limitations of conventional methods, and the possible development of novel control methods in the context of AMR. This information will significantly contribute to the development of clinical applications for AMR and improve the prognosis of patients who undergo organ transplantation.